Rare, obscure and marginal affixes in English - Laurie Bauer (Lexis: Journal in English Lexicology)
English is full of words with recurrent sequences of segments which may or may not be morphologically interpretable. In this paper I look at some which fall on either side the cut-off point between morphology and non-morphology, considering what it is that makes something an affix and how we might decide in awkward cases.